2015
DOI: 10.1097/iio.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Internal Limiting Membrane Peeling During Idiopathic Epiretinal Membrane Removal

Abstract: Idiopathic epiretinal membrane (ERM) is characterized by the growth of fibrocellular tissue on the internal limiting membrane (ILM). An ERM can range from a subtle cellophane-like film that does not cause any visual disturbance to a significant, multilayered, contractile membrane with folds in the underlying and adjacent retina, causing metamorphopsia and a decline in visual acuity. Although the exact pathogenesis of ERM formation is unclear, it is known to be associated with posterior vitreous detachment 1 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
(92 reference statements)
1
3
1
Order By: Relevance
“…Visual acuity findings in our meta-analysis are likely explained by the fact that additional ILM peeling provided no improvement in functional outcomes, these findings were in consistent with the previous review,39 but contrast to a recent meta-analysis,40 which revealed that ILM peeling group had better BCVA after surgery within 12 months, but worse BCVA in the 18th month.…”
Section: Discussionsupporting
confidence: 88%
“…Visual acuity findings in our meta-analysis are likely explained by the fact that additional ILM peeling provided no improvement in functional outcomes, these findings were in consistent with the previous review,39 but contrast to a recent meta-analysis,40 which revealed that ILM peeling group had better BCVA after surgery within 12 months, but worse BCVA in the 18th month.…”
Section: Discussionsupporting
confidence: 88%
“…However, it should be noted that the majority (11/12, 91.7%) of eyes with recurrent ERMs in our study were not visually significant, which is in agreement with prior work indicating that most recurrent ERMs are not clinically significant. 15 One possible explanation for the deviation in our results relative to prior studies is the significant presence of risk factors predisposing to ERM formation in our patient cohort, as described previously and seen in Table 1. Regardless, given the results of prior work regarding combined ERM and ILM removal and the clinical insignificance of recurrent ERMs noted herein, we are still of the opinion that removal of both ERM and ILM is still beneficial for patients choosing to undergo vitrectomy.…”
Section: Discussioncontrasting
confidence: 58%
“…The cause of its existence is not yet clear. However, it has been attributed mostly to posterior vitreous detachment (PVD) [1], which provokes glial cells (Muller) and extracellular components to accumulate and migrate on the ILM [2]. The prevalence of ERM ranges from 1.02% to 18.5% [3].…”
Section: Introductionmentioning
confidence: 99%
“…ERM is removed by the aid of a special substance which dyes the membrane on the ILM. Triamcinolone, indocyanine green and triphenylmethane (brilliant blue) are dyes which can be used during the operation [2]. The rate of recurrence of ERM formation is 10%-16.3% [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation